Pengaruh Digital Lifestyle, Kecerdasan Moral, Dan Pendidikan Etika Bisnis Terhadap Persepsi Etis Mahasiwa FEB UISU - Cindi Selvia, Cindi Selvia; Nasma Tia Miswari, Nasma Tia Miswari; Fellah Nadira, Fellah Nadira; Prihatin Saskia, Prihatin Saskia; Mas’ut (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study examines the impact of digital lifestyle, moral intelligence, and business ethics education on students' perceptions of ethics at the Faculty of Economics and Business, UISU. A sample of 60 participants represented the entire population. Research data were collected through a survey distributed using purposive sampling techniques. The statistical techniques used include classical assumption tests, multiple linear regression, validity analysis, and hypothesis testing, and the data were processed using the SPSS 20 statistical program. The results of the study indicate that digital lifestyle has a significant influence on students' ethical perceptions. Meanwhile, moral intelligence and business ethics education do not have a significant influence on students' ethical perceptions. These findings indicate that digital lifestyle is an important factor shaping students' ethical perceptions in the modern era, while moral intelligence and business ethics education require more effective approaches to have a significant impact on the ethical development of FEB students at the University of Islam Sumatera Utara.